2005
DOI: 10.1007/s11104-005-1328-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arbuscular Mycorrhizal (AM) Symbiosis on Phosphorus Leaching through Soil Cores

Abstract: Two experiments with soil cores were carried out to investigate the effects of arbuscular mycorrhizal (AM) fungal colonization on mobility of phosphorus (P) during leaching of repacked columns of a soil with a loamy sand texture. Trifolium subterraneum plants inoculated with an AM fungus or not inoculated were grown in cores with low or high P concentrations for 8 or 10 weeks in the glasshouse. Cores were then irrigated with 2500 mL water and the leachate collected. Plant growth and the amounts of P removed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
4
38
1
Order By: Relevance
“…Mycorrhizal colonization is usually coincide with AM external hyphal development in soil which leads to increase of N and P acquisition, transport and delivery to plant (Asghari et al, 2005;Johansen et al, 1993b;Leigh et al, 2009;Li et al, 2009;Tanaka and Yano, 2005). In our experiment roots of Phalaris aquatica were more colonized by AM fungi than Austrodanthonia caespitosa, which is in agreement with previous work (Tran and Cavagnaro, 2010).…”
Section: Leachate Volume and Nutrient Concentrationsupporting
confidence: 93%
“…Mycorrhizal colonization is usually coincide with AM external hyphal development in soil which leads to increase of N and P acquisition, transport and delivery to plant (Asghari et al, 2005;Johansen et al, 1993b;Leigh et al, 2009;Li et al, 2009;Tanaka and Yano, 2005). In our experiment roots of Phalaris aquatica were more colonized by AM fungi than Austrodanthonia caespitosa, which is in agreement with previous work (Tran and Cavagnaro, 2010).…”
Section: Leachate Volume and Nutrient Concentrationsupporting
confidence: 93%
“…In support of these ideas, van der Heijden (2010) detected a trend toward lower leachate volumes, in the presence of the AM community, for all six AM vs non-mycorrhizal contrasts he established. Asghari et al (2005) also demonstrated lower leachate volumes of AM colonized plants but did not control for the bigger size of the AM treatments.…”
Section: Mechanisms Of Am Fungal Involvementmentioning
confidence: 87%
“…In contrast, in non-metal contaminated soils a decrease in mycorrhizal colonization with soil depth was observed [33][34][35].…”
mentioning
confidence: 91%